2023
DOI: 10.1111/1759-7714.14842
|View full text |Cite
|
Sign up to set email alerts
|

Safety evaluation of immune checkpoint inhibitors combined with chemotherapy for the treatment of small cell lung cancer: A meta‐analysis of randomized controlled trials

Abstract: Background The addition of immune checkpoint inhibitors (ICIs) to chemotherapy is the new standard of care in the first‐line treatment of small cell lung cancer (SCLC). However, although the concomitant use of immunotherapy and chemotherapy can increase the antitumor efficacy, it can also increase toxicity. The present study evaluated the tolerability of immune‐based combinations in the first‐line treatment of SCLC. Methods Relevant trials were identified by searching electronic databases and conference meetin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
(68 reference statements)
0
2
0
Order By: Relevance
“…Mei et al (31) identified 33 RCTs and found that camrelizumab or avelumab combined with chemotherapy showed higher incidences of all-grade AEs, whereas durvalumab and sintilimab could be considered relatively safe PD-L1 and PD-1 inhibitors. Longo et al (16) identified seven RCTs and found that ICI-based combined treatment was associated with a high risk of grade 3-5 trAEs in patients with small cell lung cancer. Hao et al (32) showed that ICIs + nab-paclitaxel/paclitaxel were associated with a lower risk of irAEs than that seen with ICI monotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mei et al (31) identified 33 RCTs and found that camrelizumab or avelumab combined with chemotherapy showed higher incidences of all-grade AEs, whereas durvalumab and sintilimab could be considered relatively safe PD-L1 and PD-1 inhibitors. Longo et al (16) identified seven RCTs and found that ICI-based combined treatment was associated with a high risk of grade 3-5 trAEs in patients with small cell lung cancer. Hao et al (32) showed that ICIs + nab-paclitaxel/paclitaxel were associated with a lower risk of irAEs than that seen with ICI monotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Several systematic reviews and meta-analyses have investigated ICI adverse effects on cancer at specific sites and found that the use of ICIs could increase the risk of toxicity and treatment discontinuation (13)(14)(15)(16)(17). The increased risk of AEs is a challenge in the development of novel ICIs, especially for combined treatments in clinical practice (18).…”
Section: Introductionmentioning
confidence: 99%
“…Small cell lung cancer (SCLC) accounts for approximately 14% of all lung cancers [ 1 , 2 ]. Immune checkpoint inhibitors (ICIs) in combination with chemotherapy have become the new standard of care for the first-line treatment of extensive-stage SCLC, such as durvalumab plus platinum and etoposide [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Given the potential incidence of adverse events associated with immunotherapy [15], it becomes imperative to determine whether ES-SCLC patients with brain metastases can derive maximal benefit from this treatment approach. The existing inconsistencies in the literature underscore the necessity for a systematic review aimed at evaluating the treatment outcomes of first-line immunotherapy combined with chemotherapy in ES-SCLC patients with varying brain metastasis statuses.…”
Section: Introductionmentioning
confidence: 99%